Having Bad Social Life Conditions in Mickey's Thanatophobia in Mickey 17 Film (2025) - Muchammad Daffa Firzatullah; Rommel Utungga Pasopati; Kusuma Wijaya (Menulis: Jurnal Penelitian Nusantara, 2026)
This study examines how bad social life conditions contribute to the development of thanatophobia in the main character, Mickey Barnes, in Bong Joon Ho’s film Mickey 17 (2025). Thanatophobia refers to the fear of death and the anxiety related to mortality. Using a qualitative descriptive method and applying Ernest Becker’s theory of death anxiety, this research analyzes selected dialogues, scenes, and character interactions that reflect social degradation, economic instability, dehumanization, and authoritarian control. The findings reveal that Mickey’s poor social environment marked by economic desperation, manipulation, violence, disposability, and loss of autonomy intensifies his awareness of mortality and reinforces his existential anxiety. The study concludes that Mickey’s fear of death does not emerge merely from repeated physical deaths, but from the social system that treats him as replaceable and strips him of human dignity.